REAL-TIME FINANCIAL PERFORMANCE MONITORING AT PT SARANA MULTI INFRASTRUKTUR: ENHANCING DECISION-MAKING THROUGH DATA INTEGRATION - Mico Suryo Atmahadi; Sylviana Maya Damayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Indonesia’s infrastructure development has expanded rapidly, especially with PT Sarana Multi Infrastruktur (PT SMI) mandated by the Ministry of Finance to support various national projects. Despite its crucial role, PT SMI faces persistent challenges in monitoring financial performance in real-time due to fragmented data systems and manual processes. These issues lead to reporting delays, reduce decision-making speed, and create compliance risks. This study aims to identify the root causes of these problems and propose a practical solution. Using qualitative methods, including semi-structured interviews with top executives (CEO, CFO, and CRO), focus group discussions, and process mapping, the research applied the Current Reality Tree (CRT) method to map core issues. The analysis revealed three main problems: scattered data with no single source of truth, excessive manual steps, and unclear data governance. To address these, the study developed three improvement scenarios (conservative, moderate, aggressive) and validated them using the Delphi method with internal experts. The moderate scenario, which emphasizes centralized data management, automation, and real-time dashboards, was most preferred. The study proposes an implementation roadmap using Scrum methodology, ensuring a structured, flexible approach to enhance financial monitoring at PT SMI.